Chronic exogenous ketone supplementation blunts the decline of cardiac function in the failing heart. (6th October 2021) - Takahara, Shingo; Soni, Shubham; Phaterpekar, Kiran; Kim, Ty T.; Maayah, Zaid H.; Levasseur, Jody L.; Silver, Heidi L.; Freed, Darren H.; Ferdaoussi, Mourad; Dyck, Jason R.B.
Abstract: Aims: Recent evidence has demonstrated that ketone bodies, particularly β‐hydroxybutyrate (BHB), are beneficial to the failing heart due to their potential as an alternative energy substrate as well as their anti‐inflammatory and anti‐oxidative properties. Exogenous supplementation of ketones also helps prevent heart failure (HF) development in rodent models, but whether ketones can be used to treat HF remains unexplored. Herein, we investigated whether chronic supplementation of ketones is beneficial for the heart in a mouse model of established HF. Methods and results: To elevate circulating ketone levels, we utilized ( R )‐3‐hydroxybutyl‐( R )‐3‐hydroxybutyrate [ketone ester (KE)]. C57Bl/6N male mice were subjected to transverse aortic constriction (TAC) surgery. After developing HF, mice were treated with either 20% KE or vehicle via drinking water for 2 weeks. In another cohort, mice 3–4 weeks post‐TAC received acute intravenous infusions of BHB or saline for 1 h and their cardiac function was measured. 20% KE significantly elevated blood BHB in mice ( P  < 0.01) without inducing ketoacidosis or altering other metabolic parameters. Mice with overt HF (30–45% ejection fraction) treated with 20% KE displayed significantly elevated circulating ketone levels compared with vehicle‐treated mice ( P  < 0.05). The significant cardiac dysfunction in mice with HF continued to worsen after 2 weeks of vehicle treatment, whereas this decline was absent in KE‐treated mice (mean difference 4.7% ejection fraction; P  < 0.01). KE treatment also alleviated TAC‐induced cardiomyocyte hypertrophy ( P  < 0.05) and reduced the TAC‐induced elevated cardiac periostin ( P  < 0.05), a marker of activated fibroblasts. Cardiac fibrosis was also significantly reduced with KE treatment in TAC mice ( P  < 0.01). In another cohort, acute BHB infusion significantly increased the cardiac output of mice with HF ( P  < 0.05), providing further support that ketone therapy can be used to treat HF. Conclusions: We show that chronic treatment of exogenous ketones is of benefit to the failing heart and that chronic ketone elevation may be a therapeutic option for HF. Further investigations to elucidate the underlying mechanism(s) are warranted.